Multiparametric ultrasound imaging characteristics of multiple testicular adrenal rest tumours in congenital adrenal hyperplasia. (February 2022) - Mansoor, Nina M; Huang, Dean Y; Sidhu, Paul S
Introduction: Testicular adrenal rest cell tumours (TART) are rare benign adrenocorticotropic hormone-dependent testicular tumours, which can develop in patients with congenital adrenal hyperplasia. If left untreated, they can cause testicular tissue damage and infertility. Ultrasound is the imaging modality of choice allowing for non-invasive diagnosis provided that characteristic features are seen. In recent times, magnetic resonance imaging characteristics have also been described to aid diagnosis. Case Report: This case describes the imaging features of multiple bilateral TART in a young patient with congenital adrenal hyperplasia. Traditional greyscale and colour Doppler ultrasound demonstrated intratesticular, predominantly hypoechoic areas, with increased surrounding colour Doppler flow. In addition, contrast-enhanced ultrasound and strain elastography were performed, showing increased TART vascularisation and increased stiffness in the hypoechoic areas. Subsequent magnetic resonance imaging confirmed bilateral lobulated, well demarcated, intratesticular lesions, which appeared predominantly isointense on T1-weighted imaging, hypointense on T2-weighted imaging, with heterogeneous enhancement following gadolinium administration. Discussion: This case illustrates the sonographic features including greyscale, colour Doppler, contrast and elastography ultrasound of TART in a patient with congenital adrenal hyperplasia. Both contrast-enhanced ultrasound and elastography can provide information about tissue properties not normally derived from conventional ultrasound and aid accurate diagnosis. Additional magnetic resonance imaging is not normally required with typical ultrasound appearances. The unusual findings seen on the ultrasound examination were likely secondary to poor compliance with treatment. Conclusion: Familiarity and recognition of characteristic and uncommon imaging features of these tumours are important to avoid misdiagnosis and surgical intervention.